COMBINATION OF IRRITABLE BOWEL SYNDROME WITH ANXIETY PHOBIC SYNDROME DURING PREGNANCY AND THE EFFECTIVENESS OF MEDICAL PSYCHOLOGICAL SUPPORT IN IT - Gafurova, S.Sh. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2025)
This article presents an analysis of the results of measures to identify anxiety-phobic disorders observed in irritable bowel syndrome during pregnansy , improve medical psychological support, and treat disorders in the patient's psyche using psychotherapy methods. A statement was made about the importance of psychotherapeutic support in irritable bowel syndrome and achieving the intended result in a short time.